Salmonella serovars associated with human salmonellosis in Brazil (2011-2020) (Research, Society and Development, 2022)
Salmonella is one of the major foodborne pathogens worldwide. Domestic, wild animals, and a variety of food matrices can transmit Salmonella spp. to humanS. Here, we report the top 10 Salmonella serovars isolated from human sources between 2011 and 2020 and received in the National Reference Laboratory for Enteric DiseaseS. Serotyping was performed according to the Kauffman-White scheme. 3113 isolates related to human cases belonging to 61 serogroups were received in the NRL between 2011 and 2020. The purpose of this article is the identification of circulating serotypes as the first step to understanding the epidemiology, and then, with this information, take actions to mitigate and control this pathogen.